167k views
2 votes
Convert the following to standard form, then write

the quadratic term, the linear term, and the constant
term in the space provided:
f(x) = (x + 3)2

1 Answer

3 votes

Answer:


f(x)=x^2+6x+9

Explanation:

We are required to represent the expression given in the standard form to the quadratic form

Given


f(x) = (x + 3)^2

let us square the given expression

f(x)=(x+3)(x+3)

open brackets


f(x)=x^2+3x+3x+9

sum the similar terms


f(x)=x^2+6x+9

User Tzivia
by
4.9k points